2015
DOI: 10.25100/cm.v46i1.1570
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of the in vitro granulomatous response to Mycobacterium tuberculosis H37Ra

Abstract: Background: The hallmark of tuberculosis is the granuloma, an organized cellular accumulation playing a key role in host defense against Mycobacterium tuberculosis. These structures sequester and contain mycobacterial cells preventing active disease, while long term maintenance of granulomas leads to latent disease. Clear understanding on mechanisms involved in granuloma formation and maintenance is lacking.Objective: To monitor granuloma formation and to determine gene expression profiles induced during the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In this way, researchers hope to characterize the immunopathological changes consistent with productive infection leading to latency. in vitro granuloma models have been developed to study M. tuberculosis [29,[68][69][70][71][72][73][74][75][76], M. leprae [77], M. bovis [78], M. massiliense [79], and Map [44]. Unique iterations of the M. tuberculosis model were used to investigate resuscitation from latency [69,76], consequences of macrophage polarization [71], and effects of cytokine suppression on granuloma development [74].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, researchers hope to characterize the immunopathological changes consistent with productive infection leading to latency. in vitro granuloma models have been developed to study M. tuberculosis [29,[68][69][70][71][72][73][74][75][76], M. leprae [77], M. bovis [78], M. massiliense [79], and Map [44]. Unique iterations of the M. tuberculosis model were used to investigate resuscitation from latency [69,76], consequences of macrophage polarization [71], and effects of cytokine suppression on granuloma development [74].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that one third of the human population is infected with Mtb, predominantly in latent state. Only 10% of those infected with Mtb develop active TB disease over their lifetime, while 90% of otherwise healthy humans remain in a latent state following infection [ 4 , 5 ]; however the percentage of those with latent infection that develop active disease increases if they are immunocompromised, e.g., HIV or diabetes [ 1 ]. Inhaled bacteria that enter the lung airway and are ingested by alveolar macrophages which are highly regulated in their immune responses, and their ability to destroy digested bacteria is limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that lymphocytes in human PBMCs aggregates around infected bacteria to form assembly of micro-granulomas [34]. Furthermore, micro-granulomas are formed specifically in response to Mtb , whereas other microbes such as E.coli and S. aureus did not form these structures when incubated with human PBMCs [37].…”
Section: Resultsmentioning
confidence: 99%